Factors impacting English teachers’ creativity in teaching English as a foreign language in Indonesia - Didin Nuruddin Hidayat; Fitriah Fitriah; Mahlil Mahlil; Jon Mason (Studies in English Language and Education, 2023)
Teachers bring various experiences to the classroom, and their beliefs about ‘creative teaching’ or ‘good teaching’ practices are frequently influenced by various factors, including their own teaching experiences, individual motivation, and organizational constraints. This context frames their early efforts to develop creative practices, and recognition of influences further affects the level of creativity displayed by teachers. This study aims to ascertain the factors that affected teachers’ creativity in English language teaching (ELT) in contemporary Indonesian higher education. We interviewed twenty Indonesian English as a Foreign Language (EFL) teachers about the factors influencing their creativity and their motivations for teaching creatively. We identified three factors which influenced teachers’ creativity: their knowledge and teaching experiences, their motivation, and the role of technology. These three factors served as a guide for teachers regarding how they might integrate creativity into their teaching practice. Additionally, Indonesian EFL teachers believed that their creativity was necessary to assist students in learning, create an enjoyable learning experience, and encourage students to be creative. This belief appears to be partially due to the affordance of the rapidly changing digital environment which enables student-centred and self-directed learning. Finally, this study indicates that creativity is not instinctive to teachers; however, they can nurture their creativity by accepting their innovative ideas through developing their abilities to teach creatively.